Gerrymandering Threat To American Democracy - Ghadbane , Djihan; Benfenniche, Bouchra; Cherfaoui, Samia (University of Ammar Theledji -Laghouat, 2020)
Every ten years, The United States redraw congressional districts that elect the 435 members of the House of Representatives after the decennial census data has been collected and organized. Politicians around the country have taken to using these map revisions for their party’s own political gains and have been doing so since the time even before the United States Constitution was ratified. This process where politicians draw district lines to favor their own party and expand their political power is called gerrymandering. The purpose of this mixed method study is to understand the impact gerrymandering has on democracy in the United States, examining six states specifically at the federal level, the six states examined for this study are Pennsylvania, North Carolina, Wisconsin, Iowa, Arizona, and Washington State. A qualitative analysis of the literature triangulated with a GIS spatial analysis of the six states answers whether or not specific locations in the US can be characterized as less democratic based on their political geography, as well as a discussion of how maps that are not gerrymandered could be drawn